KONTRIBUSI PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA PALEMBANG - Sultan Asyrof Aliftiqhor; Rinol Sumantri (CV. Cendekiawan Muda Sriwijaya, 2024)
This study aims to analyze how much the parking tax contributes to Palembang City's Original Revenue in 2017-2021 and to find out the Islamic Economics review of the parking tax contribution in increasing Palembang City's Original Revenue. The analytical method used in this study is a qualitative method with data collection techniques in the form of interviews, documentation, archives and journals and articles from several sources. The results of this study show that the average contribution of parking tax to the local revenue of Palembang City in 2017-2021 is 2.57% and is categorized as having a very low contribution because the percentage level is less than 10%. The highest contribution rate of parking tax occurred in 2018 and the lowest contribution rate of parking tax occurred in 2020. According to an Islamic economic perspective, the contribution of the parking tax in increasing local revenue in the city of Palembang is in accordance with Islamic economic values, such as the presence of elements of justice, transparency, accountability and openness and the benefits of tax collection can be directly felt by the community through infrastructure development and other facilities so as to realize the benefit of the people.